Dynamika zmiany PKB a wahania konsumpcji na przykładzie wybranych krajów Unii Europejskiej - Rydarowska-Kurzbauer, Joanna (Gospodarka w Praktyce i Teorii, 2012)
The turn of century was full of dynamic and multi-dimensional changes in the global economy. The most spectacular phenomena may include financial crises. They exerted influence not only on the economy, in which they appeared, but as a result of deepening of globalization spread "infecting" others. The purpose of this article was an attempt to find similarities in the dynamics of changes in production and global demand that characterized the economy of selected European Union countries. From the viewpoint adopted for the choice of test method. Information on the selected countries were gathered by analysis of statistical data. The starting point was to show the dynamics of gross domestic product (GDP) in selected countries and to find similarities between them. In the next section, attention was focused on the changes in the component of aggregate demand: consumption and particularly on its correlation with the rate of change of GDP. For analysis and comparisons were selected following the economy: the economy of the European Union (represented by the euro area) and the economie of Central and Eastern Europe. For countries - representatives of Central and East European adopted mainly due to historical and geographical reasons, apart from Polish, Czech, Hungary and Slovakia. Completed a brief summary of the article indicating that the main conclusions of the analysis.